2004
DOI: 10.1634/stemcells.22-5-759
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Immune Suppression as Adjunctive Therapy for In Utero Hematopoietic Stem Cell Transplantation in Nonhuman Primates

Abstract: In utero hematopoietic stem cell transplantation could potentially be used to treat many genetic diseases but rarely has been successful except in severe immunodeficiency syndromes. We explored two ways to potentially increase chimerism in a nonhuman primate model: (a) fetal immune suppression at the time of transplantation and (b) postnatal donor stem cell infusion. Fetal Macaca nemestrina treated with a combination of the corticosteroid betamethasone (0.9 mg/kg) and rabbit thymoglobulin (ATG; 50 mg/kg) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Nonhuman primates have similar stem and progenitor cell dynamics when compared to humans and have been invaluable in developing and assessing new therapeutic transplant approaches for the treatment of human diseases (16)(17)(18)(19). Studies with nonhuman primates that have focused on hematopoietic stem cell (HSC) transplantation and gene marking indicate outcomes that closely parallel those from human clinical trials (16,20).…”
Section: Introduction B One Marrow Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…Nonhuman primates have similar stem and progenitor cell dynamics when compared to humans and have been invaluable in developing and assessing new therapeutic transplant approaches for the treatment of human diseases (16)(17)(18)(19). Studies with nonhuman primates that have focused on hematopoietic stem cell (HSC) transplantation and gene marking indicate outcomes that closely parallel those from human clinical trials (16,20).…”
Section: Introduction B One Marrow Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…However, successful intrauterine haematopoietic stem cell transplants have only been achieved in the immunodeficient fetus, suggesting that there may still be an immunological barrier. Studies have shown an allogenic response from 9–12 weeks of gestation, the magnitude of response increasing with gestational age, 18 adding weight to the theory that failure in the non‐immunodeficient fetus may be due to graft‐versus‐host reaction as reported in animal models 19 . Human leukocyte antigen compatibility may thus be important in the success of fetal stem cell transplantation.…”
Section: Medical Therapymentioning
confidence: 99%
“…In the absence of immunosuppression, only microchimerism has been achieved in human fetal recipients or nonhuman primate models of IUHCT. [1][2][3][4][5][6] These levels are too low for the correction of most diseases and have not been demonstrated to predict tolerance. The reasons for this failure are unclear and reflect a limited understanding of the engraftment barriers involved in clinical IUHCT.…”
Section: Introductionmentioning
confidence: 99%